5-Benzyl-4-Phenyl-2,4-Dihydro-1,2,4-Triazole-3-Thione - Akkurt, M.; Öztürk, Seyfullah; Servi, S.; Cansiz, A.; Şekerci, M.; Kazak, C. (Int Union Crystallography, 2004)
As part of structural studies of 1,2,4-triazole derivatives, the crystal structure of the title compound, C15H13N3S, has been investigated. The structure shows a V-shape in the molecular skeleton, as found for similar compounds. The crystal structure is stabilized by an N-H⋯S and three C-H⋯π intermolecular interactions. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.